(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Acute febrile illness is the most common clinical presentation among patients attending to doctor in developing countries. In Bangladesh, dengue and typhoid fever have emerged as major public health problems. Co-infection with both these diseases is rarely reported and are known to present with overlapping symptoms making the clinical diagnosis difficult. The exact incidence of dengue and typhoid co-infection is not known. Here we report a case of co-infection of dengue fever with typhoid fever. Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 96-97